Routine Head Computed Tomography for Patients in the Emergency Room with Trauma Requires Both Thick- and Thin-Slice Images - Kazuhide Maetani; Jun Namiki; Shokei Matsumoto; Katsutoshi Matsunami; Atsushi Narumi; Toshimi Tsuneyoshi; Masanobu Kishikawa (Emergency Medicine International)
Background. Images of head CT for the supratentorial compartment are sometimes recommended to be reconstructed with a thickness of 8–10 mm to achieve lesion conspicuity. However, additional images of a thin slice may not be routinely provided for patients with trauma in the emergency room (ER). We investigated the diagnostic sensitivity of a head CT, where axial images were 10 mm thick slices, in cases of linear skull fractures. Methods. Two trauma surgeons retrospectively reviewed head CT with 10 mm slices and skull X-rays of patients admitted to the ER that were diagnosed with a linear skull fracture. All patients had undergone both head CT and skull X-rays (n=410). Result. The diagnostic sensitivity of head CT with a thickness of sequential 10 mm was 89% for all linear skull fractures but only 56% for horizontal fractures. This CT technique with 10 mm slices missed 6% of patients with linear skull fractures. False-negative diagnoses were significantly more frequent for older (≥55 years) than for young (<15 years) individuals (p=0.048). Conclusions. A routine head CT of the supratentorial region for patients in the ER with head injuries requires both thick-slice images to visualize cerebral hemispheres and thin-slice images to detect skull fractures of the cranial vault.